MAKING OF MINI MUFFIN JEWAWUT AS MUFFIN INNOVATION FROM LOCAL - Fitri Rahmawati, Nabila Chrismawati (Prosiding Pendidikan Teknik Boga Busana, 2020)
Muffins are bakery products originating from the UK and are now widely known by the people of Indonesia. Muffins are classified as quick breads, which are bakery products that are made without going through the fermentation process. Muffins use flour as raw material. The high level of use of wheat flour has caused a high amount of flour imports in Indonesia. According to BPS (2009), during 2009 the amount of flour imported by Indonesia was ± 256 million tons. To overcome this, bakery products that do not use wheat flour are currently being developed but using flour derived from agricultural products in Indonesia, one of which is millet. Millet flour has a high component of dietary fiber content which is 8.21% and low amylose content 6.96% -9.29 (so it is sticky and low development rate). These components can affect the physical properties of mini muffins such as the color, taste, and organoleptic properties of mini muffins. The main ingredients of this mini muffin are medium protein wheat flour and the ingredients for making mini muffins substituted with tepung jewawut are butter, icing sugar, egg, fresh milk, milk powder, baking powder, cinnamon powder, chocolate block. The research design used was a randomized block design (RBD) with a single factor, namely the substitution rate of flour by millet flour with 3 levels, namely 15%, 35%, and 50%. The parameters tested were water, ash, fat, total protein, crude fiber, and carbohydrates by diff with total carbohydrates 51.58% and 51.21% which took 2 replications. The results showed that substitution of millet flour gave a significant effect with Î± = 50%. Keywords: mini muffins, wheat flour, millet flour